English Teachers Gendered Identities Constructions in their Doings, Sayings and Relatings - Rodriguez, Angela Milena (Colombian Applied Linguistics Journal, 2022)
This is a research report of a feminist poststructuralist discourse analysis study carried out in a private University in Tunja, Boyacá, Colombia. This study intended to explore the relation among two EFL university teachers’ pedagogical practices and their gendered identities constructions. Pedagogical practices were framed in the practice architectures: doings, sayings and relatings proposed by Kemmis & Mutton (2012) It was unveiled that doings, sayings and relatings were sites for and outcomes of teachers´ gendered identities construction. Additionally, teachers´ gendered sayings, doings and relatings were interweaved, juxtaposed, complemented, and contrasted sites where teachers performed different masculinities and femininities based on their capacities to adapt, resist, contest and oppose to heteronormative and patriarchal discourses such as gender roles and normative masculine and feminine features. Those gendered constructions were identified to have possible consequences upon students´ English language leaning and gendered identities construction.